Digital tools for computer music production and distribution - Politis, Dionysios; Tsaligopoulos, Miltiadis 1949-; Iglezakis, Ioannis 1965- (Advances in multimedia and interactive technologies (AMIT) book series, 2016)
This book presents research-based perspectives and solutions for integrating computational methods for music production, distribution, and access around the world in addition to challenges facing the music industry in an age of digital access, content sharing, and crime